Are married and unmarried Yemeni people differ in their perception of family concept and its function? - Basaleem, Huda; Al-Sakkaf, Khaled (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction In Yemen, conservative social traditions are the norms. Yemen has one of the highest population growth rate and the highest rate of unmet need for family planning (FP) in the world. This study aimed to explore the perception and attitude about family concept and its planning among married and unmarried people in selected Yemeni Governorates. Methods The study was conducted in April-May 2014 through house to house community-based cross-sectional survey with a purposively selected sample in 21 districts in 3 Yemeni governorates. The target population was Yemeni citizens aged 15+ years present in households in the targeted districts at the time of data collection. Married and un married respondents were approached equally with a pre-tested questionnaire and only consented respondents were enrolled. Results Analysis was done using the statistical package for Social Sciences version 22. Differences between married and unmarried respondents was tested by Chi squared test (χ²). Statistical significance was set at p˂0.05. The study involved 2217 respondents. Married and unmarried respondents were not different in their perception and attitude regarding family size, the negative influence of large family size, the relation of family size to children education and age at marriage, and some economic aspects in relation to large family size. However, they differently perceive the meaning of the family; reasons for establishing the family and for having children; decision makers for continuation of children education; reasons for postponing marriage, the influence of having too male children on increasing family income and on boosting father’s prestige amongst others. Conclusions In conclusion, married and unmarried were not different in most of the addressed issues. The few differently perceived issues reflect differences in life experience, reality and social responsibilities. There is a need for further studies to monitor practices related to demographic changes over time in the Yemeni society.